2014
DOI: 10.1186/s12898-014-0027-3
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal helminths may affect host susceptibility to anthrax through seasonal immune trade-offs

Abstract: BackgroundMost vertebrates experience coinfections, and many pathogen-pathogen interactions occur indirectly through the host immune system. These interactions are particularly strong in mixed micro-macroparasite infections because of immunomodulatory effects of helminth parasites. While these trade-offs have been examined extensively in laboratory animals, few studies have examined them in natural systems. Additionally, many wildlife pathogens fluctuate seasonally, at least partly due to seasonal host immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 76 publications
(93 reference statements)
0
16
0
Order By: Relevance
“…Across countries and continents, anthrax dynamics are often seasonal, although this may range from predictable annual outbreaks to sporadic, high-mortality epizootics 12,23,[28][29][30][31] . The timing and intensity of seasonality are far from consistent across space, even on the same continent 1,5 , and the underlying drivers are a complex product of local climate and soil conditions, herbivore community structure and seasonal movement dynamics, and co-morbidity with other pathogens 23,[32][33][34] . Several recently advanced spatiotemporal modelling methods can capture and infer complex seasonal drivers of zoonotic spillover 35,36 , but in application to anthrax, these models would be most appropriate at spatial scales where these drivers are consistent across the landscape 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Across countries and continents, anthrax dynamics are often seasonal, although this may range from predictable annual outbreaks to sporadic, high-mortality epizootics 12,23,[28][29][30][31] . The timing and intensity of seasonality are far from consistent across space, even on the same continent 1,5 , and the underlying drivers are a complex product of local climate and soil conditions, herbivore community structure and seasonal movement dynamics, and co-morbidity with other pathogens 23,[32][33][34] . Several recently advanced spatiotemporal modelling methods can capture and infer complex seasonal drivers of zoonotic spillover 35,36 , but in application to anthrax, these models would be most appropriate at spatial scales where these drivers are consistent across the landscape 37 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, zebra in Etosha National Park in Namibia experience peaks in infection during the warm wet season (March-April), whereas elephants are more likely to be infected during the dry months of October-November [35]. A definitive explanation for these peaks remains elusive, but a number of alternatives have been proposed, including nutritional stress, heterogeneous soil ingestion rates [33], and complex coinfection dynamics [39,40].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…A similar key problem is that anthrax infections exist in an ecosystem of pathogens, and the within‐host role that co‐infection plays in anthrax immunology is complicated at best. Field studies in Etosha have shown apparent trade‐offs in zebra between helper T cell class 1 (Th‐1) and 2 (Th‐2) type immune responses, where Th‐2 responses seem to peak in the wet season in response to gastrointestinal helminths (Cizauskas et al ., ). These immune responses appear to make zebra and springbok more tolerant of helminth infections when they peak during the wet season, decreasing host resistance to anthrax infection and thereby potentially contributing to the overall seasonality of anthrax outbreaks (Cizauskas et al ., ).…”
Section: Anthrax: a Case Study In Slow Integrationmentioning
confidence: 97%